Evaluation of Argyreia speciosa root extract as a protective agent against cyclophosphamide-induced toxicities - Alkesh Patel, Hardik Koria, Diwyanshi Zinzuvadia, Rushikumar Shah, Urmit Patel, Nandini Patel, Vithal Deshpande, Bhavna Parwani (Journal of Applied Pharmaceutical Science, 2023)
Cyclophosphamide (CYP), an alkylating anticancer drug, is one of the main chemotherapy drug used to treat variety of cancers that are linked to severe organ toxicities. Due to clinical manifestation on a wide range of organ systems, toxicities place restrictions on dose escalation needed to treat advanced stages of cancer. The current investigation aims to determine the protective effect of Argyreia speciosa (AS) root extract against CYP-induced cardiotoxicity, testicular toxicity, gastrointestinal toxicity, and haematotoxicity. The methanolic and aqueous extracts were prepared by maceration method and the toluene extract was prepared by soxhlet extraction methods. Adult male Wistar rats were divided into five groups: control, CYP (100 mg/kg) treated, CYP (100 mg/kg) + amifostine (200 mg/kg) treated, CYP (100 mg/kg) + low dose of AS root extract (100 mg/kg) treated, and CYP (100 mg/kg) + high dose of AS root extract (300 mg/kg) treated. AS root extract protects CYP-induced damages in cardiac, testicular, and gastrointestinal tissue but hematological results do not show a significant difference. AS enhances the antioxidant defense of the body, reduces cellular damage and abnormal histomorphological alterations. The low dose of AS (100 mg/kg) is found to be effective in mitigating and preventing the toxicities induced by CYP.
Keywords: Cyclophosphamide, Argyreia speciosa, cardiotoxicity, gastrointestinal toxicity, haematotoxicity, testicular toxicity